THE POLITICAL ECONOMY OF INDONESIA'S CYBER RESILIENCE: STRATEGIC GAPS IN THE PRIVATE SECTOR AND CRITICAL INFRASTRUCTURE IN FACING ADVANCED PERSISTENT THREATS (APTS) - Afif, Muhammad Fawwaz; Sumadinata, R. Widya Setiabudi; Wibawa, Satriya (International Journal of Cultural and Social Science, 2026)
This research focuses on analyzing cybersecurity threats to Indonesia in the context of digital political-economic transformation, particularly following the implementation of nickel downstreaming policies and the strengthening of Indonesia's position in the global supply chain for critical minerals. This study aims to examine the structural linkages between national industrial policy, the escalation of Advanced Persistent Threats (APT) activity, the failure of public-private partnerships, stagnant cybersecurity regulations, and the limitations of Indonesia's cyber diplomacy in responding to transnational threats. This research uses a qualitative approach with a case study method, relying on analysis of policy documents, cyber threat intelligence reports from 2023-2025, academic publications, and critical reviews of strategic events such as the ransomware attack on the Temporary National Data Center. The results indicate that the cyber threats facing Indonesia are systemic and rooted in global political-economic dynamics, where downstreaming policies and dependence on foreign technology create strategic incentives for foreign actors to conduct cyber espionage against strategic industrial sectors. This study also finds weak public-private collaboration due to a trust deficit, regulatory uncertainty, and the absence of incentives for incident reporting, which leads to the state's partial blindness in understanding the national threat landscape. Furthermore, the stagnation of the Cybersecurity and Resilience Bill and the limitations of regional cyber diplomacy highlight the gap between the rhetoric of digital sovereignty and the operational capacity of states. The implications of this research emphasize the urgency of strengthening integrated cybersecurity governance, regulatory reform that balances security and civil rights, and reorienting public-private partnerships as the foundation of cyber resilience.